Pengaruh Pendapatan Valuta Asing Dan Biaya Promosi Terhadap Laba Di PT. Bank Muamalat Periode 2015-2019 - Dede Yusuf Hidayat; Nunung Nurhasah; Didit Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
In this study aims to examine the effect of foreign exchange earnings and promotional costs on profits of PT. Bank Muamalat. The data source in this study is secondary data in the form of published financial reports. The analysis of this method uses multiple regression with SPSS data processing techniques. From the analysis test states 1) There is a significant positive effect of Foreign Exchange Income and Promotion Costs. In the multiple linear regression test, the calculated F value is 8.339, higher than F table 3.49, the significance level is 0.003 <0.005, which means that there is a significant positive effect simultaneously. Personally, the Foreign Exchange Income variable provides a coefficient value of 3.516 with a sigma of 0.003 which means that it has a significant positive effect and Promotion Costs of 2.309 with a sigma of 0.034, which means that it has a significant positive effect. Keywords : Foreign Exchange Earnings; Promotion Costs; Profit